1998
DOI: 10.1021/bi9815243
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of a Conserved Asparagine to the Conformational Stability of Ribonucleases Sa, Ba, and T1,

Abstract: The contribution of hydrogen bonding by peptide groups to the conformational stability of globular proteins was studied. One of the conserved residues in the microbial ribonuclease (RNase) family is an asparagine at position 39 in RNase Sa, 44 in RNase T1, and 58 in RNase Ba (barnase). The amide group of this asparagine is buried and forms two similar intramolecular hydrogen bonds with a neighboring peptide group to anchor a loop on the surface of all three proteins. Thus, it is a good model for the hydrogen b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 72 publications
(108 reference statements)
3
67
0
Order By: Relevance
“…These mutations were modeled using Swiss-PDBViewer 66 and the percent burial of the carboxyl oxygens were calculated using pfis 37 (Table 7). Substitution of these glutamines with glutamic acid would have allowed the carboxyl oxygens to be more exposed to solvent.…”
Section: Results For Position 76 Apply Elsewhere In Rnase Samentioning
confidence: 99%
See 2 more Smart Citations
“…These mutations were modeled using Swiss-PDBViewer 66 and the percent burial of the carboxyl oxygens were calculated using pfis 37 (Table 7). Substitution of these glutamines with glutamic acid would have allowed the carboxyl oxygens to be more exposed to solvent.…”
Section: Results For Position 76 Apply Elsewhere In Rnase Samentioning
confidence: 99%
“…Position 76 in RNase Sa and neighboring turn residues (Ala75, Gln77, and Glu78). The side chain of Thr76 is 2.5% hyper-exposed to solvent as determined by pfis 37 . The figure was generated using the Swiss-Pdb Viewer program 66 .…”
Section: Solubility Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal Denaturation-The thermal denaturation of RNase Sa and all of the single mutants studied to date is reversible and closely approaches a two-state folding mechanism (15,26,28). Thermal denaturation curves were determined and analyzed as described above, and the results are presented in Table II.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously compared the stability of RNase Sa and two close relatives, RNase Sa2 and RNase Sa3, and determined the pH and salt dependence of their stability (25). We have shown that a conserved Asn residue (26) and the Tyr -OH groups (15) make large contributions to the stability of RNase Sa. We have studied the contribution of charge-charge interactions to the stability of RNase Sa (27).…”
mentioning
confidence: 99%